Dynamic Response of Anisotropic Multilayered Road Structures Induced by Moving Loads Based on a Novel Spectral Element Method - Wang, Yan; Lin, Gao; Li, Zhiyuan (Buildings (Basel), 2022)
This contribution is devoted to the analysis of three-dimensional elastodynamic problems in multilayered road systems caused by moving loads with static and dynamic components. For this purpose, a novel spectral element method (SEM) is derived to model the layers of a road and the half-space. To reduce the order of wave equations, a state vector is introduced, and then a state transition matrix is derived for the upper and lower boundaries of a layer. Based on the use of a precise integration algorithm (PIA), very accurate numerical solutions can be obtained. The proposed method was derived within 3D Cartesian coordinates, which facilitate the analysis of complex loads or road structures. The stiffness matrix does not depend on tedious and lengthy analytical solutions, which is conducive to the analysis of anisotropic materials. Numerical examples are presented and compared with those of previous studies to show the accuracy and effectiveness of the proposed SEM. Additionally, this model is further refined by examining the effects of moving load speed and the properties of the road on the displacement and stress field of a stratified flexible pavement.